Magnetic entropy change and magnetocaloric effect of DyNiSi3, Dy2Ni3Si5, DyNiSi2 and HoNiSi0.33Ga67 antiferromagnets. (April 2019) - Morozkin, A.V.; Yapaskurt, V.O.; Yao, Jinlei; Nirmala, R.; Quezado, S.; Malik, S.K.
Abstract: Magnetic properties, magnetic entropy change and magnetocaloric effect of the polycrystalline SmNiGe3 -type DyNiSi3, U2 Co3 Si5 -type Dy2 Ni3 Si5, CeNiSi2 -type DyNiSi2 and CeCu2 -type HoNiSi0.33 Ga0.67 antiferromagnets have been studied by bulk magnetization measurements. In field of 100 Oe DyNiSi3, Dy2 Ni3 Si5, DyNiSi2 and HoNiSi0.33 Ga0.67 show Néel temperature (TN ) of 21 K, 19 K, 9 K and 4 K, respectively. At 2 K, above critical field (Hcrit ) of 28 kOe for DyNiSi3, 10 kOe for Dy2 Ni3 Si5, 25 kOe for DyNiSi2 and ∼1 kOe for HoNiSi0.33 Ga0.67 they are soft ferromagnets and HoNiSi0.33 Ga0.67 shows ferromagnetic ordering below TC  = 5 K in a field of 5 kOe. Magnetic entropy changes (ΔSm ) of DyNiSi3, Dy2 Ni3 Si5, DyNiSi2 and HoNiSi0.33 Ga0.67 exhibit high-temperature negative and low temperature positive components around Néel temperature up to critical field with decreasing and disappearance of positive component of ΔSm above critical field, which indicates the transformation from antiferromagnetic to ferromagnetic states. From these compounds, HoNiSi0.33 Ga0.67 shows largest magnetic entropy change of −15.4 J/kg⋅K at 8 K for a field change of 0–50 kOe. Graphical abstract: Image 1 Highlights: DyNiSi3, Dy2 Ni3 Si5, DyNiSi2 and HoNi0.33 Ga0.67 are metamagnets. They show field-sensitive antiferromagnetic ordering at 21 K, 9 K, 26 K and 4 K. They show HT negative and LT positive components of ΔSm around Néel temperature. They exhibits only negative ΔSm above critical field. ΔSm of HoNiSi0.33 Ga0.67 reaches −15.4 J/kg⋅K at 8 K in field of 50 kOe.